2003
DOI: 10.1046/j.1440-1711.2003.t01-1-01174.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel CD44 antibody identifies an epitope that is aberrantly expressed on acute lymphoblastic leukaemia cells

Abstract: Summary Previous studies have shown that the antibody 7H9D6 identifies CD44, a glycoprotein receptor for hyaluronic acid. 7H9D6 recognizes an epitope of CD44 that is not always present on CD44 molecules. The 7H9D6 antibody bound to the hyaluronic acid binding domain of CD44 and inhibited cell adhesion to immobilized hyaluronic acid. However, the expression of the 7H9D6 epitope was not sufficient for hyaluronic acid binding. Immunofluorescent staining with 7H9D6 revealed a punctate surface staining pattern, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…CD44 is involved in binding and internalizing pericellular HA through proteolytic cleavage that enables the intracellular domain to translocate to the nucleus and regulate gene transcription and also rapidly transport HA to lysosomes for degradation . In this study CD44 was detected with an antibody, clone Hermes‐1, that binds to the HA binding region in the link module of CD44 in the extracellular region . Analysis by flow cytometry indicated that cells exposed to either HA‐nanoceria or nanoceria exhibited decreased expression of this region of CD44.…”
Section: Discussionmentioning
confidence: 82%
“…CD44 is involved in binding and internalizing pericellular HA through proteolytic cleavage that enables the intracellular domain to translocate to the nucleus and regulate gene transcription and also rapidly transport HA to lysosomes for degradation . In this study CD44 was detected with an antibody, clone Hermes‐1, that binds to the HA binding region in the link module of CD44 in the extracellular region . Analysis by flow cytometry indicated that cells exposed to either HA‐nanoceria or nanoceria exhibited decreased expression of this region of CD44.…”
Section: Discussionmentioning
confidence: 82%
“…The failure of the transduced NALM6 cells to adhere to hyaluronic acid is consistent with the failure of pre-B ALL cells to bind this ligand despite expressing CD44. 6 None of the cell lines adhered significantly to collagens I or IV or to hyaluronic acid and all three cell lines bound similarly to fibronectin and laminin. All three cell lines adhered weakly to the osteoblastic cell lines, U2OS and SAOS-2 but strongly to Dexter stroma, fibroblasts and the bone marrow endothelial cell line HBMEC60 (data not shown).…”
Section: To the Editormentioning
confidence: 87%
“…All antibodies were used as recommended by the manufacturer. FMC63-biotin was prepared as previously described (29) from material purified from hybridoma culture supernatant on protein G columns. SDF-1a was purchased from Peprotech (Rocky Hill, NJ) or from Philip Owen (University of British Columbia, Vancouver, British Columbia, Canada).…”
Section: Methodsmentioning
confidence: 99%